2005
DOI: 10.5194/adgeo-2-7-2005
|View full text |Cite
|
Sign up to set email alerts
|

Detecting trends of extreme rainfall series in Sicily

Abstract: Abstract. The objective of the study is to assess the presence of linear and non linear trends in annual maximum rainfall series of different durations observed in Sicily. In particular, annual maximum rainfall series with at least 50 years of records starting from the 1920's are selected, and for each duration (1, 3, 6, 12 and 24 h) the Student's t test and the MannKendall test, respectively, for linear and non linear trend detection, are applied also by means of bootstrap techniques. The effect of trend on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
39
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 13 publications
8
39
0
2
Order By: Relevance
“…The results obtained with the three methods of fitting for the extreme value analysis, Gumbel moments, GEV moments, and GEV-L moments are almost the same, confirming the findings of Bonaccorso et al (2005). The choice of the RP was also not critical, as the analysis was focused on change detection rather than on value estimation.…”
Section: Annual Rainfall Maxima Trend Analysissupporting
confidence: 72%
See 2 more Smart Citations
“…The results obtained with the three methods of fitting for the extreme value analysis, Gumbel moments, GEV moments, and GEV-L moments are almost the same, confirming the findings of Bonaccorso et al (2005). The choice of the RP was also not critical, as the analysis was focused on change detection rather than on value estimation.…”
Section: Annual Rainfall Maxima Trend Analysissupporting
confidence: 72%
“…A comparison of nine global GCMs shows a tendency towards an increase in 1884 SIMONE FATICHI AND ENRICA CAPORALI extreme events (Tebaldi et al, 2006). Scientific observations also indicate that an increase in extreme rainfall events is observable in many areas all around the world, including northern and southern Italy (Hopkins and Holland, 1997;De Michele et al, 1998;Mason et al, 1999;Brunetti et al, 2000;Fowler and Kilsby, 2003;Groisman et al, 2004;Bonaccorso et al, 2005). Even in Tuscany, a region located in central Italy, some authors have identified signals of climate change by analyzing extreme rainfall and hailstorms (Crisci et al, 2002;Piani et al, 2005).…”
Section: Commission Of the European Communitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is essential to conduct extreme rainfall trend analysis at finer temporal scales, since urban flash flooding is the product of heavy rainfalls over short durations. Studies addressing non-4 stationarity in extreme rainfall events are very rare in the literature for sub-daily temporal scales (Bonaccorso et al 2005, Rosenberg et al 2010, Jacob et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…However, extreme rainfall trends can show large variations over short durations (Bonaccorso et al 2005). Therefore, it is essential to conduct extreme rainfall trend analysis at finer temporal scales, since urban flash flooding is the product of heavy rainfalls over short durations.…”
Section: Introductionmentioning
confidence: 99%